Dielectric Properties and Energy Storage Densities of Poly(vinylidenefluoride) Nanocomposite with Surface Hydroxylated Cube Shaped Ba0.6Sr0.4TiO3 Nanoparticles - Liu, Shaohui (2016)
Ceramic-polymer nanocomposites, consisting of surface hydroxylated cube-shaped Ba0.6Sr0.4TiO3 nanoparticles (BST–NPs) as fillers and poly(vinylidenefluoride) (PVDF) as matrix, have been fabricated by using a solution casting method. The nanocomposites exhibited increased dielectric constant and improved breakdown strength. Dielectric constants of the nanocomposite with surface hydroxylated BST–NPs (BST–NPs–OH) were higher as compared with those of their untreated BST–NPs composites. The sample with 40 vol % BST–NPs–OH had a dielectric constant of 36 (1 kHz). Different theoretical models have been employed to predict the dielectric constants of the nanocomposites, in order to compare with the experimental data. The BST–NPs–OH/PVDF composites also exhibited higher breakdown strength than their BST–NP/PVDF counterparts. A maximal energy density of 3.9 J/cm3 was achieved in the composite with 5 vol % BST–NPs–OH. This hydroxylation strategy could be used as a reference to develop ceramic-polymer composite materials with enhanced dielectric properties and energy storage densities.